Peningkatan Hasil Belajar Siswa pada Pembelajaran Tematik Terpadu Tema 2 Menggunakan Model Active Learning Type Team Quiz di Kelas V SDN 05 Koto Tangah Kabupaten Agam - Insani, Suci Nurul; Lena, Mai Sri (Universitas Negeri Padang, 2021)
The research todescribe the improvemen of laerning-outcomes in theme 2 with active learning type team quiz model in class V SDN 05 Koto Tangah, Agam Regency. This research is an action research of the class room (PTK) that uses a qualitative approach and a quantitative approach. This activity made by two cycle on the proccess, namely cyrcle I consisting of 2 time meet and cycle II in 1 meeting. The subjects in this study were class V teacher as observer, researcher as praktitioners, and grade V students at SDN 05 Koto Tangah Agam Regency, amounting to 18 people. From this study, proved the incraese, they are: a) the results of the RPP observation in the first cycle were 84.08%, and increase at the secondcycle to be 93.18%. b) also from teacher activity were 84.37% in the first cycle, and increasing to 93.75% in the second one. c) the results of student activity in cycle I 83.33%, increased in cycle II to 91.66%. d) assesment of students' laerning-outcomes, inthe first cycle was 76.73 average, with a percentage of 61.11%, then on the second cycle be 86.14increased which 83.33% precentage. Based on these results we know that active laerning model type team quiz can improve integrated thematic learning outcomes.